KONSEP ISLAM TENTANG ADAT: Studi Analisi Adat menurut Imam Syafi, Maliki, Hanafi dan Hambali - Faiz Zainuddin (LP2M Universitas Ibrahimy, 2018)
The need for a very complete and fluctuating society is impossible to make the codification of the law perfectly. One of the difficultiy is the difference between local customs that are not the same as the customs of the old (Arab customs). The change here is not only about values alone but also can affect changes to religious (Islamic) law. The results of this study indicate that custom can be used as a Hujjah in Islamic law as long as there are not Sharih explanation of a particular case, contradicting the qhat'iy proposition of muqayyad (not absolute, and typically (uncommon) nash. Based on the results of this study, it is advisable to the legal practitioners when they want to decide on the law, put to their customs forward rather than directed to the customs other than them, so that it can provide a verdict that can be undertaken by the community.